The Future of the Suburban City Lessons from Sustaining Phoenix - Gammage, Grady (Island Press/Center for Resource Economics : Imprint: Island Press, 2016)
As a Phoenix native, the author argues that the suburban city, which grew up based on the automobile and the single‑family home, needs to dramatically change and evolve in an era of climate change. He shows how this is possible, and that many suburban cities are already making strides in increasing their resilience. Gammage focuses on the story of Phoenix, which shows the power of collective action - government action - to confront the challenges of geography and respond through public policy. He examines issues facing most suburban cities around water supply, heat, transportation, housing, density, urban form, jobs, economics, and politics. This book is a realistic yet hopeful story of what is possible for any suburban city.